STUDY THE EFFECT OF ZIRCONIUM ADDITION ON HOT CORROSION RESISTANCE OF ALUMINA FORMING AUSTENITIC STAINLESS STEEL ALLOY FE-20NI-14CR-6AL-1.2TI-0.2C AT 900OC - Rizqi Ramadhan Fatih, Muhammad
The increasing population of Indonesia makes the need for electricity increases. To meet this national electricity needs, the role of the energy industry is needed such as power plants, in June 2020 the total electrical energy produced was 70,964 megawatts (MW). Almost 50% electricity was produced by Electric Steam Power Plants (PLTU) which utilize coal combustion and natural gas that produces steam to drive turbine to produce large amounts of electricity. One of the most important components in a steam power plant is a superheater, so the use of materials for superheater components must have high efficiency, good mechanical properties, creep resistance, oxidation and corrosion resistance by molten salt and stable microstructure. In this research will be researched and studied the cyclic hot corrosion resistance with coated test in molten salt 75 wt% Na2SO4 dan 25 wt% NaCl on Fe-20Ni-14Cr-6Al-1.2Ti-0.2C (%mass) alloy with variations of zirconium 0 wt% (Z0), 0.25 wt% (Z0,25), 0.5 wt% (Z0,5), and 0.75 wt% (Z0,75) at temperature of 900oC. A series of experiments were carried out to study the hot corrosion resistance of Fe-20Ni-14Cr-6Al-1,2Ti-0.2C alloys. The experiment started with the making of alloy buttons using a mini DC electric arc furnace and then homogenized using a horizontal tube furnace. The button is then cut and polished before being tested for hot corrosion using a horizontal tube furnace at a temperature of 900oC. From a series of experiments, the weight change per surface area of the alloy was obtained. Furthermore, the characterization of the hot corrosion test results using X-Ray Diffraction (XRD) and Scanning Electron Microscope (SEM) – Energy Dispersive Spectroscopy (EDS) to determine the appearance of the microstructure with the composition and content of chemical elements. The results showed that the alloy Fe-20Ni-14Cr-6Al-1.2Ti-0.2C had an austenite matrix (Fe-?) with B2-(Fe,Ni)Al precipitates, TiC carbides, and laves phase. The highest value of hardness of the homogenized alloy is the Z0,75 alloy with a value 320.49 HV because the precipitate is small and evenly distributed. The oxide products formed are Fe1-xO, Fe2O3, Fe3O4, NiO, Cr2O3, Al2O3, TiO2, ZrO2, and NiCr2O4. In addition, there is also internal sulfidation which indicates the mechanism that occurs is high temperature hot corrosion. Zirconium plays a role in increasing the adhesion of the protective oxide of the sample thereby increasing the hot corrosion resistance. The best hot corrosion resistance is the Z0,5 alloy with an average value of dW/A0 = -0.0189 g/cm2.